Genre Analysis of International Conference Paper Abstracts - Djuwari Djuwari (Belantika Pendidikan, 2018)
The study consists of two parts. The first is to describe the moves, the language function, the most dominant language function, and verbs of process function in the abstracts. The second is to explain how the linguistic elements (grammatical categories), three modalities (certain, probable, and possible), and the non-linguistic elements support the rhetorical and logical moves and the language functions operating in the abstracts. As it is a genre analysis of international conference paper abstracts, the data were taken from the specific discourse community of international conference paper abstracts of SEAAIR conference. Theoretically, this study contributes to a fuller understanding of research on genre of international conference paper abstracts, particularly written by the discourse community of SEAAIR.